Hubungan Motivasi Kerja dan Kinerja Guru Honorer Sekolah Menengah Atas Negeri - Rina Setiowati; Teguh Triwiyanto; Wildan Zulkarnain; Rina Setiowati; Teguh Triwiyanto (Universitas Negeri Malang, 2022)
Abstract: This study aims to, (1) find out the motivation of teachers non goverment public senior high school in Ngawi Regency; (2) to know the performance of teachers non goverments of public senior high school in Ngawi Regency; and (3) to know the relation of work motivation and performance of teachers non goverment of public senior high school in Ngawi Regency. This research uses quantitative approach with descriptive correlational research design. Intrumen in this research use questionnaire with responder that is teachers non goverment of public senior high school in Ngawi Regency. Analysis techniques used are descriptive analysis, correlation, and simple regression analysis. The results of this study indicate: (1) work motivation of teachers non goverments of public senior high school in Ngawi Regency are at a medium level; (2) the performance of teachers non goverments of public senior high school in Ngawi Regency is at a very high level; (3) there is a significant positive correlation between work motivation and performance of teachers non goverment of of public senior high school in Ngawi Regency. Abstrak: Penelitian ini bertujuan untuk, (1) mengetahui motivasi guru honorer SMAN di Kabupaten Ngawi; (2) mengetahui kinerja guru honorer SMAN di Kabupaten Ngawi; dan (3) mengetahui hubungan motivasi kerja dan kinerja guru honorer SMAN di Kabupaten Ngawi. Penelitian ini menggunakan pendekatan kuantitatif dengan rancangan penelitian deskriptif korelasional. Instrumen dalam penelitian ini menggunakan angket dengan responden yaitu guru honorer SMAN di Kabupaten Ngawi. Teknik analisis data yang digunakan adalah analisis deskriptif, korelasi, dan analisis regresi sederhana. Hasil penelitian ini menunjukkan: (1) motivasi kerja guru honorer SMAN di Kabupaten Ngawi berada pada tingkat sedang; (2) kinerja guru honorer SMAN di Kabupaten Ngawi berada pada tingkat sedang; (3) terdapat hubungan positif yang signifikan antara motivasi kerja dan kinerja guru honorer SMAN di Kabupaten Ngawi.